2011
DOI: 10.1007/s10858-011-9486-4
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR metabolomics identification of markers of hypoxia-induced metabolic shifts in a breast cancer model system

Abstract: Hypoxia can promote invasive behavior in cancer cells and alters the response to therapeutic intervention as a result of changes in the expression many genes, including genes involved in intermediary metabolism. Although metabolomics technologies are capable of simultaneously measuring a wide range of metabolites in an untargeted manner, these methods have been relatively under utilized in the study of cancer cell responses to hypoxia. Thus, (1)H NMR metabolomics was used to examine the effects of hypoxia in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…Therefore, the occurrence and development of tumor are closely related to metabolic changes in the body [16]. Although metabolomics studies have been widely used in a variety of tumors, there are few reports using metabonomics to study biomarkers of breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the occurrence and development of tumor are closely related to metabolic changes in the body [16]. Although metabolomics studies have been widely used in a variety of tumors, there are few reports using metabonomics to study biomarkers of breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, glutamate acts as a neurotransmitter in various oxidative stress-related neurodegenerative conditions and has been linked to the development of lung injury in animal models of hyperoxia and sepsis (10,30,36). In addition, threonine levels increase in response to hypoxic injury (42), and elevated levels of tyramine have been reported following myocardial infarction, acute cystitis, and smoking (22,27,43). Further experimental work and bioinformatics analysis is required to determine the precise role of these metabolites in ischemia, oxidative stress, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Tumourigenesis and progression is initiated, or at least accompanied, by a number of metabolic changes, some of which facilitate the processes of local invasion and metastasis to distant organs. 4 The majority of cancers exhibit the ''Warburg phenomenon'' where cells demonstrate increased glycolysis leading to enhanced lactate production. [1][2][3] In addition, many authors have reported changes in choline and phosphocholine (PCho) levels in cancers.…”
Section: Introductionmentioning
confidence: 99%